Investigating the Influence of Word of Mouth on Interest in Visiting and Visiting Decisions of National Park (Journal of Namibian Studies : History Politics Culture, 2023)
This study discusses the effect of word of mouth on visiting interest and its impact on visiting decisions in the national park. Analyzing the relationship between Word of Mouth Effect and Interest in Visiting. The Influence of Word of Mouth on Visiting Decisions . The Influence of Visiting Interests on Visiting Decisions. This study uses explanatory research. Purposive sampling is the sampling technique used in this study. Questionnaires are used for data collection methods. Data analysis from this study used structural equation modeling (SEM) with the SmartPLS 3.0 software tool. The questionnaire was designed using a Likert scale of 1 to 5 and distributed via social media. The results of this study indicate that Word of Mouth has a positive and significant effect on Interest in Visiting. Word of Mouth has a positive and significant effect on visiting decisions. Interest in visiting has a positive and significant effect on visiting decisions. Based on the results of this study, it is suggested that the National Park can increase tourist visits by conducting e-woms such as through social media. In addition, it also improves the quality of the facilities provided and is more innovative by creating rides that can be liked by everyone and creates a positive experience. Furthermore those who have a positive experience will recommend to others and will be able to attract interest so that it ends in a decision to visit the National Park.